A RECONFIGURABLE METASURFACE IN THE FORM OF A FABRY-PÉROT RESONATOR, INVOLVING SEMI-TRANSPARENT MIRRORS AND A NONLINEAR DIELECTRICINSERT - Antonenko, Ye. O.; Antonenko, Yu. V.; Gribovsky, A. V.; Katrich, V. A. (Видавничий дім «Академперіодика», 2024)
Subject and Purpose. The paper is aimed at suggesting ways for implementing electromagnetic devices that would involve a nonlinear dielectric inside the structure for concentrating electromagnetic field within it at relatively low intensities of the excitation field. A representative example is offered by a Fabry-Pérot resonator with semi-transparent mirrors and a nonlinear dielectric inside.Methods and Methodology. The paper presents a fundamentally new approach to controlling the frequency response of a metasurface, and a method for protecting electronic modules from high excitation powers. The method is based on the use of nonlinear properties of a Fabry-Pérot "resonator-capacitor" containing a nonlinear dielectric in its volume. Thus, we propose a method for creating spatial filters and antenna protecting fairings capable of active reconfiguration.Results. Analysis of the results has shown that by changing the voltage across the resonator-capacitor plates it is possible to control the degree of electromagnetic field localization in the resonator volume. The frequency response of the metasurface based on the Fabry-Pérot resonator with a nonlinear dielectric inside can be reconfigured by changing the voltage applied to the resonator mirrors. The advantages provided by electrical control of the frequency-selective characteristics include an increased efficiency and possibility of integrating digitally controllable systems into antennas.Conclusions. The use of a Fabry-Pérot "resonator-capacitor"model, with a nonlinear dielectric inside, in the capacity of a reconfigurable metasurface, else as a power limiter in a variety of devices, has sufficient prospects for application in microwave transmitting systems. A special area of application for the reconfigurable Fabry-Pérot resonators is creation of broadband receive antenna systems for direction- finding. In essence, the proposed Fabry-Pérot resonator is a reflective antenna array with an ability to exhibit, conceal or alter its electrodynamic properties according to a certain algorithm. This opens up prospects for its application in "friend-or-foe" recognition systems, reflective beacons, navigation systems, etc.Keywords: Fabry-Pérot resonator; nonlinear dielectric; rectangular holes; reflection coefficient; semitransparent mirrorsManuscript submitted 27.10.2023Radio phys. radio astron. 2024, 29(2): 098-104REFERENCES1. Kochetova, L. A., Prosvirnin, S. L., Tuz, V. R., 2014. Optical bistability in a grating with slits filled nonlinear media. Prog. Electromagn. Res., 35, pp. 133—139. DOI:https://doi.org/10.2528/PIERM140126062. Tuz, V. R., Kochetov, B. A., Kochetova, L. A., Mladyonov, P. L., Prosvirnin, S. L., 2015. Two-oscillator model of trapped-modes inter- action in a nonlinear bilayer fish-scale metamaterial. Phys. Scr., 90(2), 025504. DOI: https://doi.org/10.1088/0031-8949/90/2/0255043. Tolmachev, V. A., Melnikov, V. A., Baldycheva, A. V., Berwick, K., Perova T. S., 2012. Electrically Tunable Fabry-Pérot Resonator Based on Microstructured, Si Containing Liquid Crystal. Prog. Electromagn. Res., 122, pp. 293—309. DOI: https://doi.org/10.2528/PIER110915064. Sydorchuk, N. V., Prosvirnin, S. L., Fan, Y., Zhang, F., 2019. Analysis of terahertz wave nonlinear reflection by an array of double silicon elements placed on a metal substrate. J. Phys. D: Appl. Phys., 52, 355303. DOI: https://doi.org/10.1088/1361-6463/ab236d5. Tuz, V. R., Kochetov, B. A., Kochetova, L. A., Mladyonov, P. L.,Prosvirnin, S. L., 2015. Two-oscillator model of trapped-modes inter- action in a nonlinear bilayer fish-scale metamaterial. Phys. Scr., 90(2), 025504. DOI: https://doi.org/10.1088/0031-8949/90/2/0255046. Flannery, J., Maruf, R. Al,Yoon, T., Bajcsy, M., 2018. Fabry-Pérot cavity formed with dielectric metasurfaces in a hollow-core fiber. ACS Photonics, 5(2), pp. 337—341. DOI: https://doi.org/10.1021/acsphotonics.7b011547. Fan, K., Koulakis, J., Holczer, K., Putterman, S., Padilla,W.J., 2020. Ultrathin Metasurface Wavelength-Selective Mirror for Mil- limeter/Terahertz Wave Fabry-Pérot Cavities. J. Infrared Millim Terahertz Waves, 41(1), pp. 365—374. DOI:https://doi.org/10.1007/s10762-019-00657-28. Pezeshki, H., and Ahmadi, V., 2013. All-optical bistable switching based on photonic crystal slab nanocavity using nonlinear Kerr effect. J. Mod. Opt., 60(2), pp. 103—108. DOI: https://doi.org/10.1080/09500340.2012.7370339. Gribovsky, A. V., 2017. A Quasi-Periodic Sequence of the Fabry-Pérot Resonators on the Basis of Planar Screens of Finite Thick- ness with Rectangular Holes. Telecommunications and Radio Engineering, 76(16), pp. 1417—1422. DOI: https://doi.org/10.1615/TelecomRadEng.v76.i16.3010. Gribovsky, A. V., and Kuzmichev, I. K., 2016. Fabry-Pérot resonator formed by two screens with rectangular holes. Radio Phys. Radio Astron., 21(1), pp. 58—64. DOI: https://doi.org/10.15407/rpra21.01.05811. Gribovsky, A. V., 2019. Sensor for Measuring the Permittivity of Solid and Gaseous Substances on the Basis of a Fabry-Perot Resonator with Evanscent Holes in the Mirrors. Telecommunications and Radio Engineering, 78(11), pp. 939—947. DOI: https://doi.org/10.1615/TelecomRadEng.v78.i11.20